Monitoring CAR T‐cells using flow cytometry. Issue 2 (25th August 2020) - Demaret, Julie; Varlet, Pauline; Trauet, Jacques; Beauvais, David; Grossemy, Aurélien; Hégo, Florent; Yakoub‐Agha, Ibrahim; Labalette, Myriam
Abstract: Background: Chimeric antigen receptor (CAR) T‐cell therapy is considered as a major scientific breakthrough in cancer immunotherapy. The success of adoptive CAR T‐cell therapy for cancer has inspired researchers to expand indications into the area of solid tumors, autoimmune and infectious diseases. The most important factors influencing outcome and durability of the response after infusion of CAR T‐cell are proliferation and persistence of this cell subset. It becomes therefore important to detect easily and monitor circulating CAR T‐cells into blood samples. Approaches such as quantitative PCR (qPCR) or flow cytometry have been developed. The aim of this study was to set up and optimize a reachable flow cytometry technique using labeled CD19 protein for the measurement of CAR T‐cells in infusion bag and patient's blood. Methods: Patients receiving Yescarta in Cell Therapy Unit (Department of hematology, Lille university hospital, France) between April and October 2019 and healthy volunteers were included to set up the flow cytometry technique. Results and conclusions: We assessed feasibility in clinic and suitability to routine workload of a flow cytometry technique to follow CAR T‐cells in infusion bag and patient's blood. With only a few manual steps, the present protocol allows the technician to perform this technique among other routine tasks, meaning a time to results of <2 hr after sample reception. We were also able to assess CAR T‐cell heterogenity in terms of CD4+ and CD8+ T lymphocytes within the subset. Moreover, this technique allows monitoring of both authority approved CD19 CAR T‐cell.